Legal Protection for Advocates in Carrying Out the Legal Profession in Indonesia - sugiarto, Edy; Rekso Wibowo , Basuki; Yusuf Hasibuan, Fauzie (Greenation Research & Yayasan Global Resarch National, 2023)
Advocates are a profession that has an important role in the law enforcement process in society. Advocates are part of the legal structure that cannot be separated from other law enforcement apparatus, such as: police, prosecutors and courts. The profession of an advocate in society is always equated with that of his clients, so that violations committed by clients are always linked to violations committed by an advocate. This can be interpreted causally as: a client's violation is the same as an advocate's violation, even though the actions carried out by the advocate are solely to carry out the client's trust and the mandate of the law. The problem raised in this research is the concept of legal immunity that can be given to advocates in carrying out the duties of the legal profession in Indonesia. The research was carried out in a normative juridical manner based on secondary data as research material so that it focused on theoretical speculative steps, normative analysis and qualitative analysis. Research results Qualification of legal immunity which can free advocates from legal sanctions in assisting clients can be carried out as long as the advocate carries out actions in the context of carrying out professional duties and functions. The good faith possessed by advocates as a basis for protection must be guaranteed in the statutory regulatory system. The binding legal relationship between advocates and clients can be used as a basis for providing legal protection to advocates while carrying out professional duties and functions. The Advocates Law substantively does not provide optimal protection against every form of legal risk that threatens the existence of the advocate profession.